Diplomasi Diplomasi Kebudayaan Italia Melalui Italian Film Festival (ITAFF) di Indonesia - ., Muthya; Fathurachmi, Enny (Department of International Relations, Universitas Mulawarman, 2025)
This article analyse Italian cultural diplomacy through film screening activities, namely the Italian Film Festival (ITAFF) held in Indonesia in 2021 and 2023 by the Italian Embassy and Istituto Italiano di Cultura (IIC) Jakarta. The purpose of this research is to describe and find out the cultural diplomacy carried out by Italy through the Italian Film Festival (ITAFF) event in Indonesia. This research focuses on two editions of the Italian Film Festival (ITAFF), namely in 2021 dan 2023. The research method used by the author is a qualitative method, with primary and secondary data collection. Primary data collection through interviews and secondary data collection through books, journals, official documents, websites, theses, articles, and internet. In analysing Italian cultural diplomacy through Italian Film Festival (ITAFF) in Indonesia, the author uses the concept of cultural diplomacy. This study found that Italian cultural diplomacy in organising the Italian Film Festival (ITAFF) fulfills the core elements of cultural diplomacy proposed by Simon Mark, namely, actors and government involvement, objectives, activities, and audiences. In these four elements, there are maximum and less than maximum elements contained in Italian cultural diplomacy through Italian Film Festival (ITAFF).